Why early exposure to language assessment matters: perceptions of fourth-semester preservice English teachers - Jiwandono, Daud; Permatasari, Riana; Novinda, Kushardiyanti; Eka Januaristi, Khairiyah (Erudita: Journal of English Language Teaching, 2025)
Although language assessment literacy (LAL) has received increasing attention globally, studies on pre-service teachers’ initial awareness in the Indonesian context are still relatively limited. This study examines the perceptions of fourth-semester pre-service English teachers toward language assessment, focusing on three main aspects: their views on the initial introduction of assessment theory, their understanding of assessment practices, and the importance of assessment. Using a qualitative descriptive design, the data were collected from 58 participants through questionnaires and semi-structured interviews with 15 participants. The results showed that the participants found the initial introduction to assessment theory to be very beneficial because it increased their self-confidence and provided a structured direction in planning their future teaching. Most participants initially viewed assessment as a tool to assess students. However, after gaining an understanding of assessment principles such as validity, reliability, practicality, and washback, their perceptions changed. They began to see assessment as an important part of the teaching process. These findings underscore the importance of incorporating language assessment literacy early in the teacher education curriculum to develop reflective and assessment-literate educators. The study recommends that language assessment instruction should not only be delivered comprehensively but also contextualized in practical teaching experiences.